PRAKTIK MOTHERLY LEADERSHIP DALAM MENGUATKAN PROFESIONALISME GURU DI SD MUHAMMADIYAH BUMIAYU KECAMATAN BUMIAYU KABUPATEN BREBES: Motherly Leadership, Profesionalisme Guru - Naza, Khoirunnaza (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2024)
The success of a school in carrying out a quality educational process is often identified with good teacher professionalism in managing existing learning, one of the efforts made is to practice motherly leadership. Mothery Leadership is a leadership practice carried out by women based on their character as a mother. The type of research used is qualitative phenomenology. Data collection using phenomenological research was obtained by observation, interviews and documentation. The results of this study are the practice of motherly leadership in strengthening teacher professionalism at SD Muhammadiyah Bumiayu divided into five discussions, first, the views of principals and teachers towards professionalism which concluded that principals and teachers must certainly have a positive view of teacher professionalism. Second, the discussion of excellent service to teachers, namely the services provided by principals to teachers so that they can work well and optimally. Third, the discussion of making and implementing rules related to teacher professionalism. Fourth, guiding and providing examples so that teachers are professional. And the fifth is following up on any criticism and suggestions related to teacher professionalism.